Structured Reporting in Neuroradiology: Intracranial Tumors - Bink, Andrea; Benner, Jan; Reinhardt, Julia; De Vere-Tyndall, Anthony; Stieltjes, Bram; Hainc, Nicolin; Stippich, Christoph (Frontiers in Neurology, 2018)
Purpose The aim of this pilot study was to assess the clinical feasibility, diagnostic yield, advantages and disadvantages of structured reporting for routine MRI-reading in patients with primary diagnosis of intracranial tumors as compared to traditional neuroradiological free text reporting. Methods A structured MRI reporting template was developed covering pathological, anatomical and functional aspects in an itemized fashion. Retrospectively 60 consecutive patients with first diagnosis of an intracranial tumor were selected from the RIS / PACS system. Structured reporting was performed by a senior neuroradiologist, blinded to clinical and radiological data. Reporting times were measured per patient. The diagnostic content was compared to free text reporting which was independently performed on the same MRI exams by two other neuroradiologists. The comparisons were categorized per item as: « congruent », « partially congruent », « incongruent » or « not mentioned in free-style report ». Results Tumor-related items: Congruent findings were found for all items (17/17) with congruence rates ranging between 98% and 39% per item. Four items achieved congruence rates ≥90%, 5 items > 80% and 9 items ≥ 70%. Partially congruent findings were found for all items in up to 50% per item. Incongruent findings were present in 7/17 items in up to 5% per item. Free text reports did not mention 12 of 17 items (range 7-43% per item). Non tumor-related items including brain atrophy, microangiopathy, vascular pathologies and various extracranial pathologies, which were not mentioned in free-text reports between 18-85% per item. Mean reporting time for structured reporting was 7:49 minutes (3:12-17:06 min). Conclusions First results showed that expert structured reporting ensured reliable detection of all relevant brain pathologies along with reproducible documentation of all predefined diagnostic items, which was not always the case for free text reporting. A mean reporting time of 8 minutes per patient seems clinically feasible.